Optimization of non-effervescent riboflavin gastroretentive floating tablets using mixture design - Arobi Katha, Umme Tabassum; Muhammad Sofwan, Sapiyan; Fatini Nasuha, Ahmad Puad; Nik Sofea Aliya, Nik Aris; Mohd Akmal, Azhar (University of Malaya, 2024)
Gastroretentive Floating Drug Delivery Systems (GRFDDS) are long-acting oral dosage forms that float on gastric juice and remain in the stomach for an elongated period gradually delivering drug substances to the upper part of the gastrointestinal system. This study aims to develop and enhance the bioavailability and stomach retention of non-effervescent riboflavin floating tablets by using a variety of polymers. In this investigation, both pre-compression evaluation and post-compression of all the tablet materials were performed according to USP specifications. In vitro, buoyancy analyses were carried out to achieve minimum floating lag time and maximum floating duration. The tablet employed direct compression methods using HPMC K17, Carbopol 940p, and polypropylene foam powder. In vitro, buoyancy studies were performed to achieve minimum floating lag time and maximum floating duration. Tablets were evaluated for physicochemical properties according to USP specifications. An optimized tablet with a floating lag time of 0.77 minutes and a floating time of 48.74 minutes was developed using Design of Experiments (DoE). The results indicated that the optimized formulation, designated as Y, performed the best. It consists of 0.45% polypropylene foam powder, 0.15% HPMC K17, and 0% Carbopol 940p. The developed non-effervescent riboflavin floating tablets have the potential to improve the bioavailability and therapeutic efficacy of riboflavin by enhancing its gastric residence time